Strategic purchasing and supply chain management - Saunders, Malcolm (FT Prentice Hall/Financial times, 1997)
This text enables readers to develop an understanding of the contribution of purchasing and supply chain management to different types of businesses and organizations, nationally and internationally. This edition examines the role of IT in purchasing and supply chain managment strategies.